Menolak Stigmatisasi (Upaya Deradikalisasi di Pondok Pesantren Modern Islam [PPMI] Assalaam Surakarta, Indonesia) - Ismail Fahmi Arrauf Nasution; Syafieh Syafieh (Universitas Darussalam Gontor, 2021)
Lately, pesantren are faced with negative stigmas that are associated as the central understanding of fundamental Islam and become the root for the emergence of radical movements in the name of Islam. This radicalism movement is considered less in line with the moderate Islamic ideology of the archipelago. So that the existence of the pesantren seems to be